INTEGRASI NILAI-NILAI KEISLAMAN PADA PEMBELAJARAN SENI BUDAYA DI MTs NEGERI 5 PADANG - Zulkifli Halim; Riki Saputra; Syaflin Halim (Universitas Muhammadiyah Pontianak, 2022)
Islamic religious education in Madrasah is a combination of several subjects that are conceptually not connected with cultural arts, because its content includes Aqidah, Fiqih, Akhlak, Quran Hadith and the history of Islamic Culture. So is the case with Cultural Arts, that it is part of a curriculum that is different from Islamic religious education. This reality is interesting to reveal how forms of integration can be carried out in internalizing Islamic religious education in cultural arts learning. Therefore, this study aims to reveal how the form of internalization of Islamic values in cultural joint learning. This research is carried out with the paradigm of constructivism, which is a qualitative research that does not recognize the truth of the observation results alone, but rather the researcher with the power of analysis constructing from the reality found. The informants of this study were teachers of cultural arts, teachers of Islamic religious education, several students who were selected with purposive techniques. Based on the results of the analysis of research data, it can be concluded that the integration of islamic values which include aqedah, worship and morals in cultural arts learning is only carried out in preliminary and closing activities. Meanwhile, in the core activities, teachers have not integrated learning materials with the values of aqedah, worship and morals. This is because teachers have difficulty finding religious material that will be integrated into the topics of discussion studied in the subject of Cultural Arts. Therefore, cultural arts teachers can integrate Islamic values in learning in aspects of media, methods or other aspects. Learning integration should not only be understood on things related to the learning material.